2017
DOI: 10.1007/s10439-017-1883-8
|View full text |Cite
|
Sign up to set email alerts
|

Methodology to Produce Specimen-Specific Models of Vertebrae: Application to Different Species

Abstract: Image-based continuum-level finite element models have been used for bones to evaluate fracture risk and the biomechanical effects of diseases and therapies, capturing both the geometry and tissue mechanical properties. Although models of vertebrae of various species have been developed, an inter-species comparison has not yet been investigated. The purpose of this study was to derive species-specific modelling methods and compare the accuracy of image-based finite element models of vertebrae across species. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…Having greater definition of the cortical shell and trabecular bone alignment also allows a better regional representation of the load transfer through the vertebrae than the more homogenized predictions seen with the direct grayscale method. This improved agreement is much stronger than the agreement found in similar studies that used a comparable methodology to the direct grayscale method and comparable to methods that used more complex, specimen‐specific material properties for each model . The conversion between grayscale and Young's modulus was comparable to studies with similar methodologies; Robson Brown et al found an equivalent conversion factor of 0.0013/GPa (0.0009/GPa in the current study), which gives a similar average bone modulus of 0.33 GPa to that of the current study, 0.25 GPa.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Having greater definition of the cortical shell and trabecular bone alignment also allows a better regional representation of the load transfer through the vertebrae than the more homogenized predictions seen with the direct grayscale method. This improved agreement is much stronger than the agreement found in similar studies that used a comparable methodology to the direct grayscale method and comparable to methods that used more complex, specimen‐specific material properties for each model . The conversion between grayscale and Young's modulus was comparable to studies with similar methodologies; Robson Brown et al found an equivalent conversion factor of 0.0013/GPa (0.0009/GPa in the current study), which gives a similar average bone modulus of 0.33 GPa to that of the current study, 0.25 GPa.…”
Section: Discussionsupporting
confidence: 66%
“…Two approaches to generating the models were compared (Figure ). In the first (“direct grayscale method”), the images were downsampled to 1 mm 3 and the resulting grayscale of each voxel was used to define the local bone elastic modulus (Figure 3A,B), similar to a method used by Zapata‐Cornelio et al In the second (“bone volume fraction” method), an initial threshold was applied to the 82‐μm image stack to segment the trabeculae from the trabecular spaces (Figure 3D). The selected threshold was determined as the mean across all specimens using the optimize threshold feature of the BoneJ plugin for ImageJ (version 1.4.1), which optimized the connectivity against the threshold value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computed tomography images were imported into Simpleware ScanIP (v 7.0, Synopsys, United States) after their greyscalevalues had been rescaled to enable the use of previously calibrated bone properties (Zapata-Cornelio et al, 2017). The rescaled CT images at each compression step were rigidly registered to the CT images of specimens in their initial preloaded state ("preloaded CT images"), using the most caudal vertebrae as reference.…”
Section: Image Processing and In Vitro Bulge Calculationmentioning
confidence: 99%
“…Bone was modelled as a linear elastic material, with element-byelement elastic modulus scaled using the underlying greyscale value of the CT image data, and Poisson's ratio of 0.3. In order to use a greyscale-based equation for the bone modulus (Zapata-Cornelio et al, 2017), the images underlying the highresolution segmentation were down-sampled to an isotropic resolution of 0.5 mm. The greyscale-based model requires first a normalisation of the greyscale to 0-255.…”
Section: Finite Element Modellingmentioning
confidence: 99%